PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BENAR SALAH BERANTAI TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMP NEGERI 1 PEKANBARU - Indah Apritasari; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is based on the low motivation of learning PPKn Grade VIII students in SMP Negeri 1 Pekanbaru. Symptoms shown by student quickly get bored in PPKn lesson assignments from 37% student, only 8 people who diligently deliver assignment on time. Only 27% of student in the class are interested ini studying PPKn, only active students are certain student, and that’s it, from the number of student in the class only 30% of student actively ask and give opinions. Student pay less attention to the material delivered because they feel bored with monotonous learning methods which are more dominated by teachers, so studnts, become less activeThat the formulation of the problem in this reseach is "Is there a significant effect of use True False Chain Learning Model (BSB) toward student motivation in learning PPKn at SMP Negeri 1 Pekanbaru? ". This study aims to determine the effect of using True False Chain (BSB) learning models toward student motivation in learning PPKn at SMP Negeri 1 Pekanbaru. This research was conducted at SMP Negeri 1 Pekanbaru in February 2019. This research was a quantitative descriptive study that was experimental.Population in This study were student of class VIII SMP Negeri 1 Pekanbaru. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was the student of class VIII student Hang Kasturi (experimental class) who where given the True False Chain learning model, and class VIII Hang Jebat (control class) were students who were given conventional method. Then data analysis using the homogeneity test and "t" test. Based on the results of research indicated that there was an effect of learning motivation between students who using True False Chain (BSB) Learning model and conventional methods in SMP Negeri 1 Pekanbaru (thitung=17,18>ttabel=3,97). Where there was an average increase in motivation in the experimental class PPKn learning from 18.81 to 23.67 and the average of PPKn learning motivation of control class from 18,82 to 21.71. Thus the hypothesis reads that there is an effect of using True False Chain learning model towards learning motivation of PPKn students at SMP Negeri 1 Pekanbaru, can be accepted.Key Words : True False Chain, Motivation Study